Implementasi Pendampingan Penggunaan E-Commerce Dalam Upaya Meningkatkan Volume Penjualan Pada UMKM Frozenfood Lancar Jaya di Kelurahan Turi, Kota Blitzar - Dina Indah Nurcahyani; Yanda Bara Kusuma (Institut Nalanda, 2023)
MSMEs are an important part of society that cannot be separated, because the presence of MSMEs is able to help improve the economic level of society. The increasingly sophisticated digital era has given rise to new habits for MSMEs to be able to keep up with existing changes. Community service activities aim to provide assistance to MSME Lancar Jaya Frozen Food, Turi Village, Blitar City in using social media and e-commerce to increase sales volume of Lancar Jaya Frozen Food. This activity aims to assist MSME actors in using and utilizing e-commerce for the advancement of their business. The method used in implementing this service is carried out in several activities, namely the survey stage to map the needs of MSMEs, FGD (Focus Group Discussion), and providing assistance in using e-commerce. The results of the assistance provided show that sales volume for frozen food products smoothly increased by 15% from January to June, by utilizing product promotions using social media and e-commerce.